Armenian-Iranian Relations 1991-2005" - Mkrtchyan, Karen (History and Culture, 2025)
The monograph “Armenian-Iranian Relations 1991-2005” by Karen Mkrtchyan, a researcher at the Department of History of the Institute of History of the NAS of the Republic of Armenia, Ph.D., presents in detail the bilateral political, economic, scientific, educational and cultural relations, as well as the role of the Armenian community of Iran, which had a certain participation in that process. The author, based on the documents of the Ministry of Foreign Affairs of the Republic of Armenia and the National Archives of Armenia, facts provided by scientific literature and a critical analysis of individual reports in scientific periodicals, has conducted a valuable comprehensive study and presented the Armenian-Iranian relations of 1991-2005 with convincing facts and comments.